Integration Model Productive Business as Embryo Oyster Mushroom in Village Klakah District Lumajang - Ainun Jariah; Fauzan Muttaqin; Nawangsih Nawangsih (LPPM of NAROTAMA UNIVERSITY, 2021)
Research Purposes : to realize Small and Medium Industries (IKM) that are globally empowered in solving social problems through product downstreaming. Design/methodology/approach: The research method is descriptive qualitative, using direct observations and interviews and documentation. Findings: The Oyster Mushroom Farmer Group has applied the management function (organizing), business administration starts to be organized by implementing the economic entity principle, has applied a more effective online marketing strategy, graphic design for the packaging of all product innovations has followed the proper provisions, especially innovation for packaging. oyster mushroom products Limitations/Implications Research: the data sources only came from the head, farmers, and processors of the